Morphological characteristics of leukemia cells in acute myeloblastic leukemia with t(8;21)(q22;q22): possible predictability of t(8;21) (Faculty of Medicine Universitas Indonesia, 2007)
The laboratory systems for chromosomal analysis or the detection of fusion genes are generally not available in Indonesia. Therefore, bone marrow (BM) morphological analysis should be developed and applied to get an accurate diagnosis. In this study the BM smears of eight (8) cases of acute myeloblastic leukemia (AML) which had already been known to have t(8;21)(q22;q22), were morphologically evaluated in order to find out the characteristics, which might be used to predict t(8;21)(q22;q22) or the presence of AML1-ETO(MTG8) fusion gene. All of the cases belonged to AML-M2. The morphological characteristics, indicative of t(8;21) were pink colored cytoplasm in mature neutrophil (75%), neutrophilic myelocytes or metamyelocytes without granules or with scarce granules (2.3%), eosinophilia (eosinophilic myelocytes and metamyelocytes) (above 5%), myelocytes with abundant granules 8.5%, and low percentage of type I blasts (below 10%). These characteristics were not observed in AML-M2 cases without t(8;21) or AML1-ETO(MTG8). The myelocytes with abundant granules have not been described so far, while other characteristics were in line with the findings of Nakamura et al (Leukemia 1997;11:651-55). (Med J Indones 2007; 16:84-8)Keywords: PML-RARA fusion gene, AML1-ETO (MTG8), myelocytes, abundant granul